1996
DOI: 10.1159/000282835
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 28-kD Calbindin-D as a New Marker for Damage to Distal Renal Tubules Caused by Cisplatin-Based Chemotherapy

Abstract: Calbindin-D, a vitamin D-dependent calcium-binding protein of 28 kD, is found predominantly in the distal tubules of the kidney and central nervous system tissues in humans. To evaluate damage to the renal tubules caused by cisplatin-based chemotherapy, levels of urinary and serum calbindin-D were determined in patients treated with cisplatin- or carboplain-based chemotherapies using a highly sensitive enzyme immunoassay system developed in our laboratory. Levels of urinary 28-kD calbindin-D were also determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 13 publications
2
20
1
2
Order By: Relevance
“…Therefore, a smaller difference between predose and postdose values of KIM-1 would be needed to classify a compound as nephrotoxic compared with calbindin. However, there was an approximately 30-fold difference in calbindin levels (normalized to creatinine) between healthy volunteers and subjects treated with cisplatin,34 that is well above the 60% intrasubject variability. Thus, none of the biomarkers should be excluded from progressing into the next steps of biomarker qualification based on intrasubject variability.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, a smaller difference between predose and postdose values of KIM-1 would be needed to classify a compound as nephrotoxic compared with calbindin. However, there was an approximately 30-fold difference in calbindin levels (normalized to creatinine) between healthy volunteers and subjects treated with cisplatin,34 that is well above the 60% intrasubject variability. Thus, none of the biomarkers should be excluded from progressing into the next steps of biomarker qualification based on intrasubject variability.…”
Section: Discussionmentioning
confidence: 84%
“…HSA is the most abundant protein in blood plasma and it is estimated that approximately 0.06% of plasma albumin is transferred into urine through glomerular filtration [22]. Several other members of class 1 have been previously examined as biomarkers of renal and urological health including calbindin [23], clusterin [24][26], A1A [27][29], and MPO [30]. Urine levels of OPN, a multifunctional protein implicated in bone remodeling and inflammation, have been associated with rheumatoid arthritis and ovarian cancer [4], [31].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Luminex assay, this assay had a lld equivalent to 100 pg/mL. While the earlier-described immunoassay detected calbindin D28K in healthy individuals [5], urinary analysis of both normal rats and human indicated that the calbindin D28K level was below the detection limit in both the MSD and Luminex immunoassay (data not shown). Furthermore, it was not possible to accurately measure urinary spiked recombinant calbindin D28K, due to the recombinant protein instability in urine.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies have demonstrated the inhibitory effect of nephro-toxicants such as Cyclosporin A on the expression of calbindin D28K in distal tubules [4]. Furthermore, urinary analysis of patients treated with Cisplatin as well as patients treated by extracorporeal shock wave lithotripsy has indicated that the expression of calbindin D28K can be increased under pathological conditions [5, 6]. The specific localization of calbindin D28K in distal tubules along with its pathophysiological release in urine makes this protein a potential biomarker for distal tubule damage.…”
Section: Introductionmentioning
confidence: 99%